MOG-Ab prevalence in optic neuritis and clinical predictive factors for diagnosis. Issue 6 (3rd October 2019) - Ducloyer, Jean-Baptiste; Caignard, Angelique; Aidaoui, Ramzi; Ollivier, Yolaine; Plubeau, Guillaume; Santos-Moskalyk, Sonia; Porphyre, Lindsay; Le Jeune, Caroline; Bihl, Lionel; Alamine, Samy; Marignier, Romain; Bourcier, Romain; et al.
Abstract : Objective: What is the proportion of antibodies to myelin oligodendrocyte glycoprotein (MOG-Ab) in optic neuritis (ON) in adults and what would be the ON presentation for which MOG-Ab should be tested? Methods: Multicentric prospective study conducted during 1 year on all patients diagnosed with acute ON in all ophthalmological units in hospitals in a region in western France. Results: Sixty-five patients were included. MOG-Ab prevalence was 14% (9/65) during an acute ON and 13% (7/55) after exclusion of patients already diagnosed with multiple sclerosis (MS) (8) or MOG+ON (2). Compared with MS and clinically isolated syndrome, MOG+ON had no female preponderance (67% of men in case of MOG+ON and 22% of men in case of MS and clinically isolated syndrome, p<0.05) were more often bilateral (44% vs 3%, p < 0.005) and associated with optic disc swelling (ODS) (78% vs 14%, p < 0.001). To predict MOG+ON, the positive predictive values (PPVs) of male sex, ODS and bilateral involvement were 29% (95% CI 9% to 48%), 41% (95% CI 18% to 65%) and 40% (95% CI 10% to 70%), respectively, while the negative predictive values (NPV) were 93% (95% CI 86% to 100%), 96% (95% CI 90% to 100%) and 91% (95% CI 83% to 99%), respectively. The combined factor 'ODS or bilateral or recurrent ON' was the best compromise between PPV (31% (95% CI 14% to 48%)) and NPV (100% (95% CI 100% to 100%)). Conclusion: Among ON episodes, MOG-Ab were found in 14% of cases. MOG+ON occurred without female preponderance and was significantly associated with ODS and/or bilateral ON. Testing MOG-Ab only in patients presenting with ODS or bilateral or recurrent ON would limit MOG-Ab tests to fewer than half of all patients without the risk of missing any MOG+ON cases.